Pengaruh Kreativitas Guru Kelas terhadap Pembelajaran Tematik Berbasis Daring - Dewi Wahyuning Hikmah; Mamluatun Ni’mah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
The aim of this research is to examine the effect of classroom teacher creativity on thematic learning at MI Nahdlatul Ulama Kraksaan. This study uses a quantitative method and uses a non-probability sampling technique (systematic sample). Respondents from this study amounted to 56 students. For data collection techniques, researchers used observation, documentation, and questionnaires/questionnaires. Statistical analysis of the data was carried out using the person product-moment correlation statistical technique. Based on the person correlation test using SPSS version 22.0. The results of this study according to data analysis, can be seen that the significance value is 0.000 and less than 0.05 (0.000 <0.05). While the results of the comparison of Rtable and Recount show the value of Rtable = 0.266 at a significance level of 5% and from the data analysis shows the value of Rcount = 0.849. From the two results, 45.4%, it can be concluded that the creativity of classroom teachers has a significant effect on thematic learning.